A novel release kinetics evaluation of Chinese compound medicine: Application of the xCELLigence RTCA system to determine the release characteristics of Sedum sarmentosum compound sustained-release pellets - Guojun Yan; Wei Sun; Yanfang Pei; Zhaogang Yang; Xiaobing Wang; Yuan Sun; Shangtian Yang; Jinhuo Pan (Elsevier, 2018)
Purpose: To establish a novel release kinetics evaluation method of Chinese compound medicine (Sedum Sarmentosum compound) with xCELLigence Real-Time Cell-based Assay (RTCA) system. Methods: Cell lines sensitive to Sedum Sarmentosum compound are screened, and cell index-time (CI-T) graphs and cell index release kinetics models are established based on the cell index (CI) monitored. The methodological studies of precision and repeatability were processed by the cell monitors system. The release profiles of the sustained-release Sedum Sarmentosum compound were determined. Consequently, the sustained-release property was characterized by the kinetic parameters based on the cell-index. Results: The accumulative release rate based on cell index of Sedum sarmentosum compound sustained-release preparation was determined and it had a good correlation with time, fitting better with First-order model, Higuchi model and Ritger-Peppas model, and fitting best with Weibull model. It indicated that the release rate is proportional with the diffusion coefficient. Conclusion: The new method of cell-index release kinetics may provide a quantitative description for the release of the multi active agents from Traditional Chinese Medicines. The application of xCELLigence RTCA system for evaluating the release kinetics of Chinese compound medicine is feasible.